Assessing the profitability and riskiness of small business lenders in the banking industry - James W. Kolari; Charles Ou; G. Hwan Shin (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
Two alternative research hypotheses concerning how small business lending affects bank profitability are tested. The specialization hypothesis argues for higher profitability than other banks due to increased focus on small business lending, whereas the diversification hypothesis Two alternative research hypotheses concerning how small business lending affects bank profitability are tested. The specialization hypothesis argues for higher profitability than other banks due to increased focus on small business lending, whereas the diversification hypothesis
Keywords: 650